علاقة البنك المركزي الأردني بالبنوك الإسلامية في الأردن - عباد, جمعة محمود (Latakia University Journal - Economic and Legal Sciences Series, 2019)
يهدف البحث إلى دراسة العلاقة بين البنك المركزي الأردني والبنوك العاملة في الأردن. وتحقيقاً لهذه الغاية تم استعراض سبل الرقابة على البنوك الإسلامية ومقارنتها بسبل الرقابة على البنوك التقليدية، فأدركنا وجود بعض الثغرات التي أثرت سلباً على أداء البنوك الإسلامية (تم بيان أبعادها في هذا البحث). ووصولاً إلى حلول من شأنها تحسين هذا الوضع، قام الباحث بدراسة مجموعة من قوانين البنوك الإسلامية المطبقة في دول عربية أخرى. وبالاعتماد على البينات التي جمعت والتحليلات التي قدمت، خرج الباحث بمجموعة من التوصيات التي قد تساهم في قيام البنك المركزي الأردني بإجراء تعديل على بعض أدوات الرقابة وإدخال عناصر جديدة فيها لصالح البنوك الإسلامية والتي قد تؤدي إلى استثمار البنوك الإسلامية للسيولة الزائدة لديها مما ينعكس على زيادة ربحيتها وزيادة نسبة العوائد التي توزعها على حسابات العملاء لديها. The objective of this research is to study the relationship between the central bank and functioning banks in Jordan. To accomplish this, we compared the controlling methods applied in the Islamic banks with those of traditional banks. We realized some gaps that negatively affected the performance of the Islamic banks, whose dimensions are also clarified here. In order to find out the solution that may improve this situation, we studied the rules followed by Islamic banks in other Arab countries. According to the data collected and to the analysis done, the study came up with some recommendations, which could lead the central bank to adjust procedure for some control instruments, allowing new elements for the benefits of the Islamic banks. This leads to an investment of excess liquidity that available with Islamic Banks. Subsequently, it is reflected in the increase of profits, and the rate of returns could then be distributed to their customer accounts.